PEMANFAATAN TANAMAN OBAT SUKU DAYAK BAKATI DI KAWASAN HUTAN ADAT DESA GUA KECAMATAN SANGGAU LEDO - Mustika Sari; Iqbal Maulana (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2023)
West Kalimantan is an area with a distribution of tropical rain forest in Indonesia which has a fairly hight diversity so that it is estimated to store various types of plants that have the potential as medicinal ingredients. Most of the Dayak Bakati people who live in customary forests in gua village Bengkayang Regency still use medicinal plants as raw materials for traditional medicines which have been passed down from generation to generation and have been going on for a long time. The purpose of this research is to find out the types, parts and ways of processing medicinal plants used by the Dayak Bakati tribe in the customary forest area of Gua Village, Sanggau Ledo District, Bengkayang Regency. Based on the results of interviews and identification in the field with communities living in customary forest areas in Sanggau Ledo District, Bengkayang Regency, there are 28 species and 24 plant families that are used as medicinal plants by the community.Â